Automated dual two-dimensional liquid chromatography approach for fast acquisition of three-dimensional data using combinations of zwitterionic polymethacrylate and silica-based monolithic columns - Hájek, Tomáš; Jandera, Pavel; Staňková, Magda; Česla, Petr (Elsevier Science BV, 2016)
A monolithic sulfobetaine polymethacrylate micro-column BIGDMA-MEDSA designed in our laboratory, shows dual retention mechanism: In acetonitrile-rich mobile phase, hydrophilic interactions control the retention (HILIC system), whereas in more aqueous mobile phases the column shows essentially reversed-phase behavior with major role of hydrophobic interactions. The zwitterionic polymethacrylate micro-column can be used in the first dimension of two-dimensional LC in alternating reversed-phase (RP) and HILIC modes, coupled with an alkyl-bonded core-shell or silica-based monolithic column in the second dimension, for HILIC x RP and RP x RP comprehensive two-dimensional separations. During the HILIC x RP period, a gradient of decreasing acetonitrile gradient is used for separation in the first dimension, so that at the end of the gradient the polymeric monolithic micro-column is equilibrated with a highly aqueous mobile phase and is ready for repeated sample injection, this time for separation under reversed-phase gradient conditions with increasing concentration of acetonitrile in the first dimension. The fast repeating reversed-phase gradients on a short silica-monolithic or core-shell column in the second dimension can be optimized independently of the actual running first-dimension gradient program. As the alternating HILIC and RP separations on the first-dimension zwitterionic methacrylate column are based on complementary retention mechanisms, the instrumental setup essentially represents two coupled two-dimensional systems. It is first time that such an automated dual LCxLC approach is reported. The novel system allows obtaining three-dimensional data in a relatively short time and can be applied not only to multidimensional gradient separations of fiavones and related polyphenolic compounds.
Automatizovaná duální dvourozměrná kapalinová chromatografie sloužící k získání trojrozměrných retenčních dat s použitím kombinace zwitteriontové polymetakrylátové chromatografické kolony a monolitické kolony na bázi silikagelu
Keywords: Multidimensional chromatography; Reversed-phase; HILIC; Monolithic columns; Polyphenolic compounds; Vícerozměrné chromatografické metody; Reverzní fáze; HILIC; Monolitické kolony; Polyfenolické látky